1995
DOI: 10.1002/jemt.1070300409
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell death and cell proliferation in embryonic stages, normal adult, and aging prostates in human and animals

Abstract: Homeostasis in the prostate is recognized to be maintained by a complex interplay between the opposing actions of cell proliferation and cell death. Growth regulatory factors that promote or inhibit cell proliferation and promote cellular death have been identified in the prostate. The integration of these forces involves cellular cooperation between the prostatic stroma and epithelium. Hormone-regulated production of growth regulatory factors by one cell type may determine growth stimulation, inhibition, or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
(65 reference statements)
0
11
0
2
Order By: Relevance
“…Proliferative activity in the rat prostate is not confined to the basal cells, which were isolated and often absent in some portions of the acini. It has been reported that the main proliferating cells in the prostate are the columnar (luminal) cells [55]. Previous researchers [56] had shown no positive relation between diabetes and development of prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Proliferative activity in the rat prostate is not confined to the basal cells, which were isolated and often absent in some portions of the acini. It has been reported that the main proliferating cells in the prostate are the columnar (luminal) cells [55]. Previous researchers [56] had shown no positive relation between diabetes and development of prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…AR is expressed in both basal and luminal cells of the prostatic epithelium where its primary role is to promote expression of genes involved in terminal differentiation, secretion and suppression of proliferation to maintain homeostasis [12,19,20,21,22,23,24]. …”
Section: The Androgen Receptor Pathwaymentioning
confidence: 99%
“…Androgens are required for prostate gland development and for prostatic function and glandular maintenance in the adult male [1]. Androgen action is mediated through the androgen receptor (AR), a ligand-activated nuclear transcription factor.…”
Section: Introductionmentioning
confidence: 99%